1999
DOI: 10.1111/j.1545-5300.1999.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Couple‐Responsible Therapy Process: Positive Proximal Outcomes

Abstract: Therapist-couple struggle vs. cooperation is linked to clinical outcome. This research conceptualizes and investigates treatment process as it relates to the occurrence of struggle versus cooperation. Models of couple-responsible and therapist-responsible process in couple therapy were developed. Couple-responsible process consists of enactments, accommodation, and inductive process. Therapist-responsible process consists of primary therapist-couple interaction, therapist interpretation, and direct instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 59 publications
2
30
0
1
Order By: Relevance
“…Instead, therapists have the demanding task of building and using alliances with both spouses while not condoning the harmful interactions of any person (Knobloch-Fedders, Pinsof, & Mann, 2007), but facilitating couples' and families' own relationships as the engine of change (Butler & Gardner, 2003;Butler & Wampler, 1999). Therefore, we see that while the detachment of Bowenian neutrality has its alliance problems, abandoning neutrality in favor of active alignment brought entirely new and equally problematic alliance complications in relational therapies.…”
Section: A Survey Of Attempts At Reconciling Alliance and Neutrality mentioning
confidence: 84%
“…Instead, therapists have the demanding task of building and using alliances with both spouses while not condoning the harmful interactions of any person (Knobloch-Fedders, Pinsof, & Mann, 2007), but facilitating couples' and families' own relationships as the engine of change (Butler & Gardner, 2003;Butler & Wampler, 1999). Therefore, we see that while the detachment of Bowenian neutrality has its alliance problems, abandoning neutrality in favor of active alignment brought entirely new and equally problematic alliance complications in relational therapies.…”
Section: A Survey Of Attempts At Reconciling Alliance and Neutrality mentioning
confidence: 84%
“…Such concerns should not be taken lightly or dismissed as invalid, as some research suggests clients may prefer a clinical process that is more inductive and accommodative and less directive (e.g., Butler & Bird, 2000;Butler & Wampler, 1999). Haley (1977) himself engaged in a lengthy discussion of the ethical ramifications of therapist behaviors perceived as untruthful or manipulative, and seemed to believe that such concerns had more to do with individual therapists rather than specific models or approaches to therapy.…”
Section: Directives and Interventions As Perturbationsmentioning
confidence: 96%
“…Conversely, therapist-responsible process exemplified by therapist-couple interaction, therapist interpretation, and direct instruction was found to decrease the perception of couple responsibility and increase therapist-client struggle, thereby contributing to less positive clinical outcomes. Thus, enactments may decrease therapist-client struggle and foster greater cooperation and collaboration, increased interactional autonomy, and more positive therapeutic outcomes by centralizing couple interaction and engagement in therapy and privileging the couple relationship as the primary agent of change (Butler & Bird, 2000;Butler & Wampler, 1999).…”
Section: Couple Enactments Conceptually and Operationallymentioning
confidence: 96%
“…Enactment utility is measured by contributing to positive therapeutic outcomes. Empirical research has found that couple-responsible process characterized by enactments, therapist accommodation, and inductive process decreases struggle and increases couple responsibility, ultimately leading to more positive clinical outcomes (Butler & Wampler, 1999). Conversely, therapist-responsible process exemplified by therapist-couple interaction, therapist interpretation, and direct instruction was found to decrease the perception of couple responsibility and increase therapist-client struggle, thereby contributing to less positive clinical outcomes.…”
Section: Couple Enactments Conceptually and Operationallymentioning
confidence: 97%